An untypical case of normal tension glaucoma - Kovalova, Alina; Ryzhova, Iryna (The Ukrainian Scientific Medical Youth Journal, 2025)
A clinical case of normal tension glaucoma in a female patient began developing at a relatively early age (30 years) and in an atypical manner—manifesting with central visual field defects, which are not characteristic signs of glaucoma. Perimetry changes were initially observed only in the left eye, gradually progressing over a 20-year period. A central absolute scotoma also developed in the right eye over the past two years. The patient underwent ophthalmological examinations (visometry, computerized perimetry, daily tonometry, gonioscopy, ophthalmoscopy, optical coherence tomography and electrophysiological testing) and was diagnosed with primary open-angle stage III normal tension glaucoma. The uniqueness of this case lies in the diagnostic challenges in identifying glaucoma due to inconsistencies with certain diagnostic criteria.